2018
DOI: 10.1115/1.4041385
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Environmental Barrier Coated Ceramic Matrix Composite Turbine Airfoil Erosion

Abstract: Ceramic matrix composite (CMC) have higher temperature durability and lower density property compared to nickel-based super-alloys which so far have been widely applied to hot section components of aero-engines/gas turbines. One of promising CMC systems, SiC–SiC CMC is able to sustain its mechanical property at higher temperature, though it inherently needs environmental barrier coating (EBC) to avoid oxidation. There are several requirements for EBC. One of such critical requirements is its resistance to part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…9,[12][13][14][15][16][17][18][19][20][21][22] However, until recently, little work has been performed on characterizing and understanding the SPE behavior of CMCs and EBCs. [1][2][23][24][25][26] Conversely, extensive work has been performed on superalloys and TBCs. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] In fact, SPE of superalloys and TBCs remains an area of active research.…”
Section: Dustmentioning
confidence: 99%
See 4 more Smart Citations
“…9,[12][13][14][15][16][17][18][19][20][21][22] However, until recently, little work has been performed on characterizing and understanding the SPE behavior of CMCs and EBCs. [1][2][23][24][25][26] Conversely, extensive work has been performed on superalloys and TBCs. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] In fact, SPE of superalloys and TBCs remains an area of active research.…”
Section: Dustmentioning
confidence: 99%
“…Fourteen years passed between the work of Singh et al 51 in 2005 and the next study on SPE of EBCs reported by Okita et al 25 in 2019. Okita et al 25 investigated the SPE behavior of an APS EBC with a Si bond coat deposited on a CMC.…”
Section: Solid Particle Erosion Of Environmental Barrier Coatingsmentioning
confidence: 99%
See 3 more Smart Citations